Analysis Of The Effect Of Job Rotation, Work Environment And Rewards On The Performance Of Education Personnel (Tendik) At Surabaya State University - Tintin Sri Puspitasari; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (SEAN Institute, 2024)
This research aims to examine the influence of Job Rotation, Work Environment, and Rewards on the Performance of Education Personnel at Surabaya State University. Using quantitative methods with a questionnaire prepared based on the Job Rotation variable (X1),EnvironmentWork (X2), Reward (X3) and Performance (Y). This research involved 53 respondents from Unesa education staff who were chosen randomly. Data analysis was carried out through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing to determine the influence of each variable on the performance of educational staff at Unesa. The research results show that Job Rotation (X1) has no significant effect on the Performance (Y) of educational staff at Surabaya State University, while the Work Environment (X2) has a positive and significant effect with a contribution of 77.8% to the variation in Performance (Y). Reward (X3) as a whole also does not have a significant effect on Performance (Y) even though there is satisfaction with cash financial awards. Therefore, further evaluation is needed on the implementation of work rotation and reward systems to make them more effective in improving performance. Unesa management needs to continue to improve working environment conditions and evaluate the job rotation and reward system to encourage optimal performance improvement.